Generating multi-partite entanglement from the quantum vacuum with a finite-lifetime mirror - Joshua Foo; Sho Onoe; Magdalena Zych; Timothy C Ralph (New Journal of Physics, 2020)
Observers following special classes of finite-lifetime trajectories have been shown to experience an effective temperature, a generalisation of the Unruh temperature for uniformly accelerated observers. We consider a mirror following such a trajectory—and is hence localised to a strictly bounded causal diamond—that perfectly reflects incoming field modes. We find that inertial observers in the Minkowski vacuum detect particles along the half null-rays at the beginning and end of the mirror’s lifetime. These particle distributions exhibit multi-partite entanglement, which reveals novel structure within the vacuum correlations. The interaction is modelled using a non-perturbative circuit model and does not suffer from energy divergences.